Cell migration in Drosophila optic lobe neurons is controlled by eyeless/Pax6. - Morante, J.; Erclik, T.; Desplan, C. (Development, 2011)
In the developing Drosophila optic lobe, eyeless, apterous and distal-less, three genes that encode transcription factors with important functions during development, are expressed in broad subsets of medulla neurons. Medulla cortex cells follow two patterns of cell movements to acquire their final position: first, neurons are arranged in columns below each neuroblast. Then, during pupation, they migrate laterally, intermingling with each other to reach their retinotopic position in the adult optic lobe. eyeless, which encodes a Pax6 transcription factor, is expressed early in progenitors and controls aspects of this cell migration. Its loss in medulla neurons leads to overgrowth and a failure of lateral migration during pupation. These defects in cell migration among medulla cortex cells can be rescued by removing DE-Cadherin. Thus, eyeless links neurogenesis and neuronal migration.